Co‐exploring relational heuristics for sustainability transitions towards more resilient and just Anthropocene futures. (29th October 2021) - Preiser, Rika; Biggs, Reinette; Hamann, Maike; Sitas, Nadia; Selomane, Odirilwe; Waddell, Joy; Clements, Hayley; Hichert, Tanja
Abstract: In this paper, four relational heuristic responses for exploring new modes of engagement, or patterns of activity, that could enliven humanity's efforts in fostering systemic thinking and action to inform sustainability transitions are offered. Their purpose is to realise more resilient and just Anthropocene futures. These relational heuristics are (1) re‐patterning our theories of change‐making, (2) cultivating a shared future consciousness, (3) creating transformative spaces and (4) engaging in processes of co‐exploration. We argue that these heuristics are better aligned for studying and responding to the systemic and interdependent nature of the real‐world challenges we are currently facing.